Correlation between Mean Corpuscular Hemoglobin, Mean Corpuscular Hemoglobin Concentration, and Fetal Hemoglobin Levels in Sickle Cell Anemia Patients of Saurashtra Region in Gujarat - Dhara P. Trivedi; Deval Mehta; Punithan Narayanan; Pragati Kantibhai Bhimani; Nidhi Saradva; Kruti Ladani; Pruthvi Gohil (Acta Medica International)
Introduction: Sickle cell anemia (SCA) is a genetic disorder characterized by abnormal hemoglobin S production. Fetal hemoglobin (HbF) levels and complete blood count (CBC) parameters are crucial in evaluating SCA. This study investigates the correlations between mean corpuscular hemoglobin (MCH), MCH concentration (MCHC), and HbF levels in SCA patients. Materials and Methods: A retrospective, observational study was conducted using data from 68 SCA patients. The study included patients with HbSS genotype, aged over 1 year, who had complete CBC and high-performance liquid chromatography data available between January 1, 2023, and January 1, 2024. Patients with incomplete data, pregnancy, recent blood transfusions, and concurrent conditions affecting blood parameters were excluded. Pearson’s correlation analysis was performed to assess relationships between HbF, MCH, and MCHC. Results: The analysis revealed significant correlations among the studied parameters. A positive correlation was observed between HbF and MCH (r = 0.243, P = 0.046). A stronger positive correlation was found between HbF and MCHC (r = 0.328, P = 0.006). The strongest correlation was observed between MCH and MCHC (r = 0.571, P < 0.001). Conclusion: The study demonstrates significant positive correlations between HbF levels and both MCH and MCHC in SCA patients. These findings suggest that elevated HbF levels may influence red blood cell indices, potentially reflecting compensatory mechanisms in SCA. The relationships observed could have implications for understanding disease severity variability and treatment responses in SCA patients.